Levels of beta-D-glucan in Candida auris supernatants, an in vitro and in vivo preliminary study. (August 2022) - Mikulska, Malgorzata; Furfaro, Elisa; Magnasco, Laura; Codda, Giulia; Giacobbe, Daniele Roberto; Dentone, Chiara; Vena, Antonio; Marchese, Anna; Bassetti, Matteo
Abstract: Objectives: Serum (1, 3)-beta-d-glucan (BDG) assay is a non–culture-based test recommended for the diagnosis of invasive candidiasis owing to its faster results and higher sensitivity than blood cultures. Its performance might vary for different Candida species. The aim of this study was to determine in vitro levels of BDG in Candida auris culture supernatants and evaluate BDG levels in patients with C. auris candidemia sustained by these stains. Methods: C. auris strains were collected from blood cultures of patients who had a concomitant (–24 to +72 hours) serum BDG test (Fungitell assay). Supernatants of broth media culture of C. auris strains and two Candida albicans (controls) strains were prepared and tested for BDG. Results: Ten C auris strains were included. Supernatants of two C. albicans considered as controls had a mean BDG level of 1155 pg/mL (considered 100% reactivity). The median BDG level in supernatants of C. auris strains was 275 pg/mL (IQR 165–523 pg/mL), with a median reactivity of 24% (range 6%–72%). In vivo, the median BDG level was 129 pg/mL (IQR, 28–199 pg/mL). Sensitivity of BDG for C. auris candidemia was 60%. All patients received antifungal treatment with an echinocandin initiated a median of 2 days (IQR –8 to 0) before blood collection for BDG. Discussion: Our C. auris strains released lower amounts of BDG when compared to C. albicans . Clinical implications include lower sensitivity of serum BDG for the diagnosis of C. auris candidemia with a consequent impact on management protocols in settings with high prevalence of this species.